2015
DOI: 10.24289/ijsser.279111
|View full text |Cite
|
Sign up to set email alerts
|

Examination of burnout level of academics in terms of demographic variables

Abstract: Akademisyenlerin tükenmişlik düzeylerinin demografik değişkenler açısından incelenmesi Examination of burnout level of academics in terms of demographic variables

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Although most of the academics in the study stated that administrative duties affect well-being in certain ways, some expressed that the positive feelings experienced during the administrative duties are not continuous and sustainable; thus, they do not affect well-being. In the literature, some studies found that the burnout levels of academics do not differ depending on whether they have administrative duties or not (Demir et al, 2015) while others revealed that the burnout levels of the academics with administrative duties are higher than those who do not have any (Azeem & Nazir, 2008;Lackritz, 2004). It can be inferred that diverse findings resulted from individual perceptions and the meaning attributed to administrative tasks, as stated by some participants of this study.…”
Section: Well-being and Administrative Dutymentioning
confidence: 52%
See 1 more Smart Citation
“…Although most of the academics in the study stated that administrative duties affect well-being in certain ways, some expressed that the positive feelings experienced during the administrative duties are not continuous and sustainable; thus, they do not affect well-being. In the literature, some studies found that the burnout levels of academics do not differ depending on whether they have administrative duties or not (Demir et al, 2015) while others revealed that the burnout levels of the academics with administrative duties are higher than those who do not have any (Azeem & Nazir, 2008;Lackritz, 2004). It can be inferred that diverse findings resulted from individual perceptions and the meaning attributed to administrative tasks, as stated by some participants of this study.…”
Section: Well-being and Administrative Dutymentioning
confidence: 52%
“…In the study, academics stated that marriage improves positive emotions as it helps them to share the burdens of life, receive support, experience happiness, feel secure and confident. This can be attributed to the fact that having a partner diminishes the struggles in life, reduces the level of burnout and negative feelings while helping cope with difficulties (Coombs, 1991;Demir, Türkmen, & Doğan, 2015). There are many findings in the literature suggesting that the levels of well-being of married individuals are higher than those who are single (Lucas, Clark, Georgellis, & Diener, 2003;Stroebe & Schut, 2015.…”
Section: Well-being and Marital Statusmentioning
confidence: 99%
“…While there is ample research examining the burnout, literature focusing on faculty burnout within universities in Turkey has been severely limited (Okray, 2018). Much of this research has concerned factors influencing burnout of faculty members, such as age, gender, academic title, teaching load, and marital status (Demir et al, 2015;Kulavuz-Önal & Tatar, 2017), personal characteristics and emotional intelligence (Arslan & Acar, 2013;Taşlıyan et al, 2014), organizational citizenship behavior and organizational silence (Çankır, 2017;Kahya, 2015). As Maslach and Jackson (1981) proposed that the primary reasons for burnout were workplace factors rather than the personal characteristics exhibited by employees, the focus of this study has been placed on the main workplace factor that might reduce the burnout of academicians: organizational climate.…”
Section: Introductionmentioning
confidence: 99%
“…This has newly created a competitive environment between private and state universities, causing new challenges to universities as well as to academic staff. While private universities have demanded that their faculties produce productivity in research as well as provide quality education and participation in administrative duties such as committee memberships, faculty members in state universities have been exposed to increased teaching and service load demands (Demir et al, 2015). These demands within both private and state universities have the potential to damage "personal and professional competencies of faculty members, reduce their productivity and lead to burnout experiences" (Sabagh et al, 2018, p. 132).…”
Section: Introductionmentioning
confidence: 99%
“…[8] examined the burnout levels of 648 academicians working in the Universities of Turkey. [16] determined that there is a significant difference in burnout levels of the academic staff in terms of some technical demographic variables in public and foundation universities in Istanbul.…”
Section: Introductionmentioning
confidence: 99%